Neural tube defects: how many cases could have been prevented in Portugal? - Braz, Paula (2021)
Abstract publicado em: European Journal of Public Health 2020 Sep;30(Suppl 5):ckaa166.964. doi: 10.1093/eurpub/ckaa166.964